Association of Antibodies to Interferon‐Inducible Protein‐16 With Markers of More Severe Disease in Primary Sjögren's Syndrome. Issue 2 (February 2016) - Baer, Alan N.; Petri, Michelle; Sohn, Jungsan; Rosen, Antony; Casciola‐Rosen, Livia
Abstract : Objective: Interferon‐inducible protein‐16 (IFI16) is an intracellular DNA receptor involved in innate immunity. We evaluated the frequency, phenotypic characteristics, and clinical associations of anti‐IFI16 antibodies in patients with primary Sjögren's syndrome (SS), and quantitated expression levels of IFI16 in SS and control salivary gland lysates. Methods: Anti‐IFI16 antibodies were assayed by enzyme‐linked immunosorbent assay using sera from patients with primary SS (n = 133) and from healthy controls (n = 47). Sera from systemic lupus erythematosus (SLE) patients (n = 132) were included as disease controls. Immunoprecipitation of in vitro transcription–translated IFI16 was used to determine which portion of IFI16 the antibodies recognized. Expression of IFI16 in salivary gland lysates was quantitated by immunoblotting. Results: Anti‐IFI16 antibodies were present in the sera of 38 of 133 SS patients (29%) compared to 1 of 47 healthy controls (2.1%) (SS versus controls; P < 0.0002) and in 31 of 132 SLE controls (24%). In SS, anti‐IFI16 antibodies were associated with an abnormal Schirmer's test ( P  = 0.003), hyperglobulinemia ( P  = 0.02), antinuclear antibody ≥1:320 ( P  = 0.01), germinal center–like structures in labial salivary gland lymphoid infiltrates ( P  = 0.01), and higher focus scores (3.4 versus 2.4; P  = 0.005). High‐titer IFI16 antibodies were directed against an epitope outside the N‐terminus in 9 of 13 SS patients (69%). IFI16 was expressed in 4 of 5 (80%) of SS and 1 of 6 (17%) of control labial salivary glands. Conclusion: Anti‐IFI16 antibodies are a prominent specificity in primary SS and are associated with markers of severe disease. IFI16 is expressed at higher levels in SS salivary glands compared to controls. These high levels in disease target tissue may contribute to the ongoing anti‐IFI16 immune response.